2002
DOI: 10.1097/00008877-200212000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety conditioned to nicotine in the elevated plus-maze is time dependent

Abstract: Conditioning to the anxiogenic effects of nicotine has previously been demonstrated in the social interaction test and there was no generalization of conditioning between the social interaction and elevated plus-maze tests. Because the two tests generate distinct states of anxiety, the conditioning could have occurred to the cues associated with the test environment and/or to those associated with the type of anxiety generated by the test. The elevated plus-maze permits separation of these two factors, because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…For example, the phenomenon of test-specific conditioned anxiety to an anxiogenic dose of nicotine has been demonstrated in both the social interaction and the elevated plus-maze tests (File et al, 2002a;Tucci et al, 2002). The corticotrophin releasing factor antagonist, a-helical CRF 9-41 reversed this conditioned anxiety, but not nicotine-induced unconditioned anxiety, providing evidence that conditioned anxiety is mediated by a different mechanism from unconditioned anxiety (Tucci et al, 2003a).…”
Section: Conditioned Anxiety and Conditioned Fearmentioning
confidence: 99%
“…For example, the phenomenon of test-specific conditioned anxiety to an anxiogenic dose of nicotine has been demonstrated in both the social interaction and the elevated plus-maze tests (File et al, 2002a;Tucci et al, 2002). The corticotrophin releasing factor antagonist, a-helical CRF 9-41 reversed this conditioned anxiety, but not nicotine-induced unconditioned anxiety, providing evidence that conditioned anxiety is mediated by a different mechanism from unconditioned anxiety (Tucci et al, 2003a).…”
Section: Conditioned Anxiety and Conditioned Fearmentioning
confidence: 99%
“…These nicotine-conditioned associations can be studied using various preclinical models [10,18,33,43]. Recently, our laboratory has employed a locomotor conditioning task with rats ( [5,7,30,31]; see also [13,32,44]).…”
Section: Introductionmentioning
confidence: 99%
“…A single immobilization leads to a rapid, but transient stimulation of TH gene transcription rate; repeated immobilization is associated with a sustained transcriptional response (Osterhout et al, 1997;Serova et al, 1999b). Furthermore, File and coworkers (Irvine et al, 1999;Tucci et al, 2002) have shown that at high doses chronic nicotine treatment is anxiogenic and consequently stressful. Hence, we have tested whether a sustained transcriptional response is observed in the LC, as well as the adrenal after repeated immobilization stress.…”
mentioning
confidence: 99%